O que nós sabemos? Da relação com o saber na e com a educação física em um processo educacional-escolar - Venâncio, Luciana [UNESP] (2014)
This Doctoral Dissertation has been developed at the research line “Formative Practices and Processes in Education” according to the following assumption: if the school is a place where people teach and learn, we can assume that the assignment of meaning is linked to relationships to knowledge that individuals settle in the time-space lived within such institution. The questions that delimit our problematics are: What is the meaning for the student to learn school Physical Education in the contemporary world? Which relationships to knowledge in Physical Education do students establish when disposal to learn? Our main objective is to understand how students attribute meanings and senses towards the relationship to knowledge developed with(in) Physical Education lessons. The specific objectives are: to identify and interpret which knowledge are elaborated by students with(in) Physical Education lessons; identify and interpret which relationships to knowledge do students establish from their experiences in Physical Education lessons; explain, analyze and interpret what is knowledge with(in) Physical Education from the participants’ perspective (teacher and students) in one shared educational practice. We deepen our discussion, in the theoretical framework, with the convergence between the theory of the notion of relationship to knowledge, based on Bernard Charlot, and the necessary knowledge for a critical and emancipatory educative practice, proposed by Paulo Freire...